Proppant transport in hydraulic fracturing: Crack tip screen-out in KGD and P3D models. (15th June 2015) - Dontsov, E.V.; Peirce, A.P.
Abstract: The aim of this study is to develop a model for proppant transport in hydraulic fractures capable of capturing both gravitational settling and tip screen-out effects, while prohibiting the particles from reaching the crack tips by imposing a width restriction based on the particle size. First, the equations that govern the propagation of hydraulic fractures and the proppant transport inside them are formulated. They are based on the solution for the steady flow of a viscous fluid, mixed with spherical particles, in a channel, which is obtained assuming an empirical constitutive model. This proppant transport model is applied to two fracture geometries – Khristianovich–Zheltov–Geertsma–De Klerk (KGD) and pseudo-3D (P3D). Numerical simulations show that the proposed method makes it possible to capture proppant plug formation and growth, as well as the gravitational settling for both geometries. A dimensionless parameter, whose magnitude reflects the intensity of the settling, is introduced for the P3D fracture.